Avaliação e caracterização das propriedades filmogênicas de proteínas do soro de leite submetidas à irradiação e modificação de pH - Fernandes, Ana Paula Stort (2014)
The packages comprise a large part of the daily disposal of household waste and these household waste are the most impactful to the environment. The development of biodegradable packaging material, seeking to replace synthetic polymers, is an approach used in an attempt to reduce the environmental impact caused by the very slow degradation of synthetic material packages. It is known that the development of biomaterials, applicable to various industries technology in the area of packaging, gaining particular attention on the issue of preserving the environment. The aim of this study was to develop a biodegradable films of whey protein irradiated subjected to pH modification, and evaluate their mechanical, optical, structural and barrier properties. The experiment was conducted in the Department of Food Engineering, College of Agronomy, Federal University of Goiás (UFG), located in Goiânia (GO). The protein concentrate, whey was supplied by the Argentine company Arla Foods. Statistical analysis was performed by analysis of variance (ANOVA) and Tukey test (p ≤ 0.05). The computer program Version 2.15.1 R (Vienna, Austria) was used for calculations. In the experiment, all analyzes were performed with three replicates read in triplicate except mechanical tests, in which three replicates were read nine times. It was found that the whey protein had an excellent alternative for the production of biodegradable films. The films were presented translucent, yellowish, with no tendency green and red colors. Movies pH 8.5 had opacity values increased with increasing doses of radiation. The films showed values of pH 5.5 solubility in water below the other, due to the proximity of the isoelectric point of proteins from whey. The pH modification and irradiation process can serve as an alternative to changing the mechanical properties of films based on whey protein concentrate milk and therefore represented an alternative raw material in the preparation of biodegradable films.